Evaluation of five questionnaires for obstructive sleep apnea screening in the elderly - Riken Chen; Jinru Zhu; Yi Yang; Weifeng Liao; Weilong Ye; Lianfang Du; Mingdi Chen; Yuan Zhang; Weimin Yao; Zhenzhen Zheng (2025)
Obstructive sleep apnea (OSA) often leads to complications in the elderly. This study compares the usefulness of five screening tools for OSA in elderly patients. Data from elderly patients diagnosed with OSA, collected from the Sleep Medicine Center of the First Affiliated Hospital of Guangzhou Medical University from January 2012 to June 2017, is analyzed. The sensitivity, specificity, predictive values, area under the curve (AUC), and diagnostic odds ratio (DOR) of the five screening tools are computed and compared. 273 elderly patients with suspected OSA are included, of whom 189 are male (69.2%). The Berlin Questionnaire has an AUC of 0.670 (95%CI: 0.611-0.725) at different cut-off points. The sensitivity and specificity of the Berlin Questionnaire are noticeably high at 0.653 (0.587-0.719) and 0.608 (0.497-0.719), 0.699 (0.621-0.776) and 0.533 (0.449-0.616), and 0.803 (0.713-0.892) and 0.503 (0.433-0.572) when the AHI is 5, 15, and 30 times/hour, respectively. The GOAL Questionnaire has the highest DOR at AHI cut-off points of 5 and 15 times/hour, while Berlin has the highest DOR at an AHI cut-off point of 30 times/hour. Comprehensive use of these five screening questionnaires for suspected OSA in elderly patients aged 60 years and older is valuable and worth promoting among the elderly population.